Citampara kṣēttira makimai : Pāṇṭiyanāyakam Śrī Cuppiramaṇiya Cuvāmi varalāṟuṭaṉ - Mācilāmaṇi, Ci. Pi (SAMP early 20th-century Indian books project ;, 1951)
On the sanctitiy of Chidambaram, Hindu pilgrimage center in Tamil Nadu.